Physical Properties of Agarophyte Gracilaria sp. (verrucosa type) from Seaweed Culture of Takalar, South Sulawesi - Agus M Hatta (Indonesian Food and Nutrition Progress, 1994)
Agarophyte of Gracilaria sp. (verrucosa type) collected from Takalar, South Sulawesi, has been studied for its quality. The organoleptic test on the raw material indicated that its color was dull red and its water content was moderate, 23.53%. The impurity content was 46.2%, and mostly consisted of very fine water soluble materials. The agar yield of the raw material was 47.70%. Its physical properties, as indicated by geling point, gel surface strength and viscosity, were inferior than commercial agar. The data suggest that impurity content is the most important determinant of agar quality. Therefore, it is recommended to improve post harvest handling to obtain better quality.